Village Economic Potential for The Implementation of Learning Building Village / KKN Thematic MBKM Program Economic Study Program Development Department of Economics, Faculty of Economics and Business of The UPN "Veteran" Yogyakarta - Sodik, Jamzani; Purwiyanta, Purwiyanta; Wijayanti, Diah Lufti (RSF Conference Series: Business, Management and Social Sciences, 2021)
The background of this research is the preparation of the Independent Learning Curriculum for the Independent Campus (MBKM) of the Development Economics Study Program. One of the mandates of the curriculum is the flexibility of the student learning process to get an off-campus learning experience for one semester (6 months), including through village building activities/thematic Real Work Lectures (KKN thematic), which are equated with the achievement of 21 credits. The purpose of this research is the availability of a thematic Village Development Activity Implementation Guide/KKN as a complement to the curriculum that has been prepared. This guide provides directions and detailed instructions for managers of study programs and their staff, students of the development economics study program (S1) who choose to learn through village building activities/thematic KKN. The problem of this research is: what are the village economic activities that can be used as objects of activities to build the thematic village / KKN. The method used to answer these problems is (1) Survey at the location of Wirokerten Village (2) Focus Group Discussion (FGD) with stakeholders (village officials, villagers, and lecturers of the Department of Economics). The results showed that village programs related to village economic development programs were sub-programs related to the field of small and medium enterprises (MSMEs) and the fields of trade and industry, which was the choice for student development study programs in the implementation of the MBKM program to build Thematic Village / KKN